2016
DOI: 10.1103/physrevc.93.014321
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensionality in atomic nuclei: A candidate for linear-chainαclustering inC14

Abstract: The clustering of α particles in atomic nuclei results in the self-organization of various geometrical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 30 publications
4
45
0
1
Order By: Relevance
“…The first band, which we call a π -bond linear chain, has two valence neutrons in a π orbit and is built on the 0 + state at 14.6 MeV which is just above the α + 10 Be threshold but below the 2α + 6 He threshold. It was found that the energies and widths of the resonances observed by the α + 10 Be elastic scattering [36,37] qualitatively agree with the theoretical calculations [15,18] including ours. Therefore, they are regarded as the π -bond linear-chain candidates, although the experimental spin-parity assignment was somewhat ambiguous.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The first band, which we call a π -bond linear chain, has two valence neutrons in a π orbit and is built on the 0 + state at 14.6 MeV which is just above the α + 10 Be threshold but below the 2α + 6 He threshold. It was found that the energies and widths of the resonances observed by the α + 10 Be elastic scattering [36,37] qualitatively agree with the theoretical calculations [15,18] including ours. Therefore, they are regarded as the π -bond linear-chain candidates, although the experimental spin-parity assignment was somewhat ambiguous.…”
Section: Introductionsupporting
confidence: 78%
“…Yamaguchi et al [39] reported the result of the α + 10 Be elastic scattering and updated the information about the candidates of the π -bond linear chain. Although the spin-parity assignments for several states are not consistent with those found in previous experiments [35][36][37]39], they first observed a candidate of the bandhead of the linear chain (J π = 0 + ), which should be compared with theoretical calculations. The other experiment was reported by Tian et al [40] and Li et al [41] who observed the resonances populated by the 9 Be( 9 Be,α + 10 Be)α reaction.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Again we see a good match of the 14 C-states which decay simultaneously into 10 Be gs and 10 Be(3.4MeV, 2 + ). Most of these resonant states have also been observed in recent resonant scattering experiment [18,19], where spin assignment were made using the angular correlation method. The states at very high energy of 23.5(1) MeV has only been identified in the present experiment, which might be an extension of the tentatively proposed molecular rotation band (see Fig.12 in Ref.…”
Section: Pos(inpc2016)035mentioning
confidence: 85%
“…Since then a number of 2n transfer or 2p removal experiments were also performed to populate the high-lying excited states in 14 C. These reactions are more sensitive to the single-particle configurations with oblate or prolate deformations [14,15,16,17]. The latest resonant α-scattering experiments are dedicated to search for cluster states in 14 C. Based on the observed resonant states some possible molecular-rotation bands or linear-chain states were proposed [18,19]. However due to the limited energy resolution of this thick-target method, the decays to 6 MeV states in 10 Be were not distinguished.…”
Section: Introductionmentioning
confidence: 99%